Developing and validating a nomogram for cognitive impairment in the older people based on the NHANES - Ma, Xiaoming; Huang, Wendie; Lu, Lijuan; Li, Hanqing; Ding, Jiahao; Sheng, Shiying; Liu, Meng; Yuan, Jie (Frontiers in Neuroscience, 2023)
Objective: To use the United States National Health and Nutrition Examination Study (NHANES) to develop and validate a risk-prediction nomogram for cognitive impairment in people aged over 60 years Methods: A total of 2802 participants (aged ≥60 years) from NHANES were analyzed. The least absolute shrinkage and selection operator (LASSO) regression model and multivariable logistic regression analysis were used for variable selection and model development. C-statisticROC-AUC, calibration curve, and decision curve analysis (DCA) were used to evaluate the nomogram's performance.The nomogram included five predictors, namely diabetes mellitussex, moderate activity, gendertaste problem, age, and education. It demonstrated satisfying discrimination with a C-statistic AUC of 0.74482 (95% confidence interval, 0.696723-0.801791). The nomogram was well-calibrated according to the calibration curve. The DCA demonstrated that the nomogram was clinically useful.The risk-prediction nomogram for cognitive impairment in people aged over 60 years was effective. All predictors included in this nomogram can be easily accessed from its' user.